Angola: tensão e discurso político - constituição do ethos discursivo e regulação do coenunciador - Mafra, Patrícia Martins (2020)
This piece of work has focus on angolan presidential discourse analysis, and, like this, analyses the ethos constitution and discoursives heterogeneities, aiming to recognize what is the “real” that favors the co-announcer’s regulation of presidential discourses. To do so, we define as corpora tension discourses from the then President José Eduardo dos Santos, in the following discoursive happening: the signature of the Lusaka Accord, in the year 1994, and the 40° anniversary of the independence of Angola, in the year 2015. In this research, we follow the theoretical perspective Discourse Analysis of french line started by Michel Pêcheux. This conception matches a scenery of debates that involves the conditions of production related to the object under study, the existing relationships between the discourse and the result of converging Linguistics, Social Studies and Psichoanalysis. Through qualitative methodology, we observe the evident ideologies using discursive formation analysis; we investigate the constitution of the discoursive ethos; we verify the effects of meaning produced in the discourses connecting the language to the exteriority; the language to the ideology and the ideology to the unconscious and, lastly, we describe the discoursive heterogeneity in the process of the co-announcer’s interpretation. Considering the results obtained, we can affirm that the perception of a unique “real” is impossible, since there is a place of justification of that “real” which is masked by the representation discourses, proposing a game of identification and exclusion in the process of interpretation, thus building a social counsciousness alienated by the dominating discourses